Status and prospects of mobile learning in general secondary education institutions (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
In the article was clarified the definition of the term "mobile learning" based on the analysis Ukrainian and foreign scientists' publications and was considered the technical improvement of mobile devices, which affects the expansion of their usage in the educational field. The concept of mobile learning is inextricably linked to the means of its implementation, which include mobile phones, smartphones, personal digital assistants, tablets. The basic characteristics that are inherent in the process of mobile learning are considered: continuity, flexibility, orientation on pupils, and freedom in location choice.  In this article mobile learning is compared with other modern pedagogical technologies, such as blended learning, distance learning, ICT-based learning by such means of communication, creation and delivery of training material, skills development, knowledge control, level of learning process continuity. The place of mobile learning in the educational process of general secondary education institutions is determined. The general advantages of mobile learning (continuous access to the educational environment anytime and anywhere, organization of online collaboration, positive impact on the pupils' motivation) and organizational difficulties (availability of material and technical background and pupils' skills) are considered. The article presents the results of a survey about usage mobile learning state in general secondary education which present that most pupils have the opportunity to use mobile technology in the classroom and have a positive attitude to the use of mobile devices during the learning process.
Keywords: blended learning; distance learning; ICT-based learning (e-learning); mobile learning (m-learning)